Open space development planning in Malaysia: Issues and problems - Ibrahim, Putri Haryati; Md Dali, Melasutra; Che Haron, Roziha (American Scientific Publishers, 2017)
This study aimed to identify and understand the problems faced by local authorities in the development planning of open spaces in Peninsular Malaysia. The study focused on the issues and problem encountered by 98 local authorities in that are governed under the Town and Country Planning Act 1976 (Act 172). To obtain information on the preparation of open spaces that involves development planning, and policy enforcement, questionnaire survey was distributed to 456 respondents which obtained a response rate of 52.6% (n=240). The study found that the availability of land, lack of funding and policy compliance are the main obstacles hindering local authorities to provide better service to the public. This study recommends several measures to address the issues in the hope that it will help the local authorities to better manage and provide long term sustainable open spaces.